BIMBINGAN ORANGTUA DALAM MENANGGULANGI ANAK TANTRUM DI LOMBOK BARAT - Musawirin Musawirin (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2018)
This study aims to determine the development of tantrum children and parental guidance in tackling Tantrum Children in Kuripan Utara Village, Kuripan Lobar District. This research is a descriptive qualitative study with a case study approach. The subject of this study is the parents of children who have the behaviour of tantrums and their neighbours. Data collection techniques used are observation, interviews, documentation. The data analysis techniques are used, namely through data reduction, data presentation, and conclusion drawing. Check the validity of the data by increasing perseverance and using source triangulation. The fndings of this study, namely the development of tantrum children in Kuripan Utara Village, have several developments including (a) physical development, (b) emotional development, (c) cognitive development, (d) social development. While the fndings of parental guidance in dealing with tantrum children are (a) moving to another place, (b) distracting the child, (c) talking softly to the child. In this parent’s guidance, the connection with the theory can produce children who will be spared from deviant behaviour when they are big.